New Attorney Bar Admission Ceremony in Wine Press Room - Watkins, Howard::::::::: (1988)
Fifth District Court of Appeal Clerk Kevin Swanson swearing in 40+ new attorneys; New attorneys include Holley Perez and Susan Coberly